2002
DOI: 10.1074/jbc.m201550200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of NADPH Oxidase-derived Reactive Oxygen Species in Generating Ca2+ Oscillations in Human Aortic Endothelial Cells Stimulated by Histamine

Abstract: There is increasing evidence that intracellular reactive oxygen species (ROS) play a role in cell signaling and that the NADPH oxidase is a major source of ROS in endothelial cells. At low concentrations, agonist stimulation of membrane receptors generates intracellular ROS and repetitive oscillations of intracellular Ca There is increasing evidence that intracellular reactive oxygen species (ROS) 1 play an important role in cell signaling(1-4). Both vascular smooth muscle cells and endothelial cells are capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…In other words, histamine stimulation increases the efficiency of [Ca 2+ ] i -oscillation-frequency-regulated VCAM1 gene expression. It is also noted that histamine-stimulated VCAM1 mRNA expression is optimized at a [Ca 2+ ] i oscillation frequency of 0.3 oscillations/minute, which is the mean [Ca 2+ ] i oscillation frequency in this type of cells upon 1 μM histamine stimulation (Hu et al, 1999;Hu et al, 2002). The distinct [Ca 2+ ] i -oscillationfrequency dependence of gene expression in the presence and absence of agonist stimulation suggests that, in addition to [Ca 2+ ] i oscillations alone, other intracellular signaling pathway(s) are also involved in agonist-stimulated gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, histamine stimulation increases the efficiency of [Ca 2+ ] i -oscillation-frequency-regulated VCAM1 gene expression. It is also noted that histamine-stimulated VCAM1 mRNA expression is optimized at a [Ca 2+ ] i oscillation frequency of 0.3 oscillations/minute, which is the mean [Ca 2+ ] i oscillation frequency in this type of cells upon 1 μM histamine stimulation (Hu et al, 1999;Hu et al, 2002). The distinct [Ca 2+ ] i -oscillationfrequency dependence of gene expression in the presence and absence of agonist stimulation suggests that, in addition to [Ca 2+ ] i oscillations alone, other intracellular signaling pathway(s) are also involved in agonist-stimulated gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that paracrine-derived superoxide triggers Ca 2+ influx in ECs (16,36,37). To examine whether the loss of gp91 phox impacts endothelial Ca 2+ entry, we pretreated ECs with thapsigargin and measured Ca 2+ entry.…”
Section: Nox2-derived Ros Activates Stim1-dependent Ca 2+ Entry In Lpmentioning
confidence: 99%
“…NAD(P)H is fluorescent and has been visualized by exciting at 340 to 365 nm and detecting emission at 400 to 500 nm (Lakowicz et al, 1992;Paul and Schneckenburger, 1996;Danø et al, 1999;Pogue et al, 2001;Schuchmann et al, 2001;Hu et al, 2002;Brachmanski et al, 2004;Blinova et al, 2005;Kasimova et al, 2006). To visualize the fluorescent signal, we used an inverted wide-field fluorescence microscope (Nikon TE-300), equipped with a CCD camera (CoolSnap HQ; Roper Instruments) mounted on the Kö hler port, and a Xenon excitatory light source (DG-4; Sutter Instruments).…”
Section: Nad(p)h Detectionmentioning
confidence: 99%
“…Their high energy status and reducing power drive many key biosynthetic reactions and ATP production. Because NAD(P)H but not NAD(P) 1 possesses an endogenous fluorescence, it is possible to detect the reduced form in living cells; this property has been widely exploited (Lakowicz et al, 1992;Pogue et al, 2001;Schuchmann et al, 2001;Hu et al, 2002;Brachmanski et al, 2004;Blinova et al, 2005;Kasimova et al, 2006). Particularly pertinent are the oscillations in NADH that have been observed in yeast cells, which serve as a marker for changes in metabolism (Ghosh and Chance, 1964;Goldbeter, 1996;Danø et al, 1999).…”
mentioning
confidence: 99%